2023
DOI: 10.1021/acsinfecdis.3c00027
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Glycosaminoglycans Are Associated with Recurrent UTI and Urobiome Ecology in Postmenopausal Women

Abstract: Glycosaminoglycans (GAGs) are linear, negatively charged polysaccharides composed of repeating disaccharide units of uronic acid and amino sugars. The luminal surface of the bladder epithelium is coated with a GAG layer. These urothelial GAGs are thought to provide a protective barrier and serve as a potential interaction site with the urinary microbiome (urobiome). Previous studies have profiled urinary GAG composition in mixed cohorts, but the urinary GAG composition in postmenopausal women remains undefined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Consisting of several layers of urothelium and an overlaying glycosaminoglycan (GAG) layer, this membrane is the most impermeable in the body, providing a barrier against the external environment and urine [1]. The GAG layer plays a key role in immune responsiveness, with altered layer composition being associated with recurrent UTIs in a cohort of post-menopausal women [2]. While mechanical and physiological barriers provide good protection against pathogen exposure, additional mechanisms are required to provide a secondary layer of defense.…”
Section: Immunological Landscape Of the Urinary Tractmentioning
confidence: 99%
“…Consisting of several layers of urothelium and an overlaying glycosaminoglycan (GAG) layer, this membrane is the most impermeable in the body, providing a barrier against the external environment and urine [1]. The GAG layer plays a key role in immune responsiveness, with altered layer composition being associated with recurrent UTIs in a cohort of post-menopausal women [2]. While mechanical and physiological barriers provide good protection against pathogen exposure, additional mechanisms are required to provide a secondary layer of defense.…”
Section: Immunological Landscape Of the Urinary Tractmentioning
confidence: 99%
“…To date, there are no other female-only studies, and there are no studies at all that examine the healthy urobiome of exclusively females across any age range. While the importance of understanding urobiome development for recurrent UTI studies in female participants is clearly shown ( 54 ), no studies have yet addressed this issue carefully in female children.…”
Section: Larger Gaps To Be Addressed In Future Studiesmentioning
confidence: 99%